ANALYSIS OF REGISTER DEALING WITH COVID â€“ 19 PANDEMIC IN THE JAKARTA POST - Fransisca Renny Ariyanti; Rr. Arielia Yustisiana (Humaniora Scientia, 2022)
This research aimed to analyse the linguistic form, types, meaning, and function of a language variation of register dealing with Covid-19 in The Jakarta Post online news published in 2020 - 2022. Register, especially related to the covid-19 case, became something interesting to be examined in The Jakarta Post online news due to the new term of a language variation during the pandemic of covid-19. This research was classified as qualitative descriptive research. The data were collected through interpretation and documentation, which contained various registers dealing with covid-19 in The Jakarta Post online news. Then, the collected data were classified based on the types of registers and the linguistics form of register. After that, the function and the meaning with contextual meaning based on the types of the register are analysed. Based on the result, seven types of registers dealing with covid-19 are found in this research. The seven types of registers dealing with covid-19 were the types of virus, types of vaccine, types of syndrome, types of test, types of countermeasure, types of carrier, and types of zone.Keywords:Â Register, covid-19, language variation, online news.